2008
DOI: 10.1021/om800397p
|View full text |Cite
|
Sign up to set email alerts
|

Base-Promoted Carbon−Hydrogen Bond Activation of Alkanes with Rhodium(III) Porphyrin Complexes

Abstract: Base-promoted carbon-hydrogen bond activation of alkanes was achieved in the reactions of alkanes with rhodium(III) porphyrin chlorides (Rh(por)Cl) at 120 °C to give rhodium porphyrin alkyls in moderate yields. This carbon-hydrogen activation (CHA) of alkane provided a facile synthesis of Rh(por)R. Mechanistic investigation of CHA suggested that Rh(por)H and [Rh(por)] 2 were key intermediates for the CHA step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 49 publications
(30 reference statements)
4
57
0
Order By: Relevance
“…The residue was purified by pipet column chromatography on silica gel with a hexane/CH 2 Cl 2 solvent mixture (7/1) as eluent. The red solid Rh(ttp)(n-pentyl) 23 Typical Procedures for the Reaction of Rh(ttp)Cl with Cyclohexyl Bromide and KOH in Air. Rh(ttp)Cl (1a; 7.8 mg, 0.0097 mmol), aqueous KOH (5.5 M, 0.0175 mL, 0.096 mmol), and cyclohexyl bromide (2a; 0.012 mL, 0.097 mmol), were added to benzene (2.0 mL).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The residue was purified by pipet column chromatography on silica gel with a hexane/CH 2 Cl 2 solvent mixture (7/1) as eluent. The red solid Rh(ttp)(n-pentyl) 23 Typical Procedures for the Reaction of Rh(ttp)Cl with Cyclohexyl Bromide and KOH in Air. Rh(ttp)Cl (1a; 7.8 mg, 0.0097 mmol), aqueous KOH (5.5 M, 0.0175 mL, 0.096 mmol), and cyclohexyl bromide (2a; 0.012 mL, 0.097 mmol), were added to benzene (2.0 mL).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The base-promoted alkane CHA by Rh(ttp)Cl [20] and other base-promoted bond activation by transition metal complexes [19,21], have prompted us to examine the promoting effect of base on the CNA of amines. However, it was found that the addition of a base was not beneficial to product yield with only 25% and 43% yields of Rh(ttp) n Bu obtained in the presence of KOH and K 2 CO 3 , respectively for the reactions between Rh(ttp)Cl and n Bu 3 N (Table 1, entries 7 and 8).…”
Section: ð1þmentioning
confidence: 99%
“…To gain an idea of the reactive intermediate and the reaction mechanism of CNA of amine, several reactive rhodium porphyrin species such as [Rh(ttp)] À , [Rh(ttp)] 2 and Rh(ttp)H were treated to react with tri-n-butylamine under the same reaction conditions [20].…”
Section: ð1þmentioning
confidence: 99%
See 2 more Smart Citations